2007
DOI: 10.1093/geront/47.5.683
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Nursing Home Performance Indicators: An Illustration Exploring the Impact of Facilities on ADL Change

Abstract: Purpose: Performance measurement systems for nursing homes assume that facility performance contributes heavily to individual outcomes. This research illustrates how that assumption can be assessed using the change in residents' activities of daily living (ADLs). Design and Methods: The data used in these analyses were all from residents with both an admission and a quarterly assessment in a sample of all admissions to a randomly chosen 10% of Medicare-or Medicaid-certified nursing homes operating during 2002.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 14 publications
2
19
4
Order By: Relevance
“…At the resident level, older age and a lower care‐need level at baseline were significantly associated with care‐need level deterioration, as documented in earlier studies …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…At the resident level, older age and a lower care‐need level at baseline were significantly associated with care‐need level deterioration, as documented in earlier studies …”
Section: Discussionsupporting
confidence: 74%
“…In addition, at the resident level, the clinical diagnosis and cognitive functioning were not considered because of the limited information in our dataset . Second, we based our findings on five functional status levels, and the very limited information might be different from previous studies, such as that carried out by Phillips et al , who based their study on ADL measures . Additionally, some research, including the present study, used care‐need level as an outcome, because the evaluation process of care‐need level is strictly carried out by the government, and a strong correlation between care‐need level and ADL was found in a previous study .…”
Section: Discussionmentioning
confidence: 90%
“…The previous studies of ADL change tested ADL outcome after 3 or 6 months after baseline (Buttar et al, 2001;Phillips, Shen, Chen, & Sherman, 2007) and the result of Phillips et al reported better explanatory power in model after 6 month than 3 month. Therefore, the outcome variable of this study was the ADL score 6 months after baseline.…”
Section: )Outcomevariablementioning
confidence: 99%
“…The majority of persons in nursing homes are lacking in one or more basic activities of daily living (ADL) (16,17). About half of the residents are over 85 years of age (18).…”
Section: Characteristics Of Nursing Home Residentsmentioning
confidence: 99%